2004
DOI: 10.1242/dev.01082
|View full text |Cite
|
Sign up to set email alerts
|

Apaf1-dependent programmed cell death is required for inner ear morphogenesis and growth

Abstract: During inner ear development programmed cell death occurs in specific areas of the otic epithelium but the significance of it and the molecules involved have remained unclear. We undertook an analysis of mouse mutants in which genes encoding apoptosis-associated molecules have been inactivated. Disruption of the Apaf1 gene led to a dramatic decrease in apoptosis in the inner ear epithelium, severe morphogenetic defects and a significant size reduction of the membranous labyrinth, demonstrating that an Apaf1-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…In addition, Gata2 has been shown to bind to Bcl-X promoter in leukemic cells (Koga et al, 2007). Bcl-X is strongly expressed in the inner ear epithelium during development at E10.5-E12.5, and its inactivation leads to developmental defects especially in the posterior duct (Cecconi et al, 2004). Here, we verified whether Bcl-X gene products were present also at E14.5 in inner ear epithelium.…”
Section: Gata2 Cko Otic Epitheliumsupporting
confidence: 60%
See 4 more Smart Citations
“…In addition, Gata2 has been shown to bind to Bcl-X promoter in leukemic cells (Koga et al, 2007). Bcl-X is strongly expressed in the inner ear epithelium during development at E10.5-E12.5, and its inactivation leads to developmental defects especially in the posterior duct (Cecconi et al, 2004). Here, we verified whether Bcl-X gene products were present also at E14.5 in inner ear epithelium.…”
Section: Gata2 Cko Otic Epitheliumsupporting
confidence: 60%
“…We did not observe any clear decrease in inner mesenchyme cell death in Gata2 cko embryos to explain the maturation defect observed. In addition, there were no evident clearance problems in the vestibule or the cochlea in the absence of programmed cell death in Apaf1-and caspase9-deficient ears (Cecconi et al, 2004 and data not shown) strongly suggesting that Apaf1/caspase9-driven apoptosis is not a major player in the perilymphatic clearance process.…”
Section: Programmed Cell Death Does Not Play a Major Part In The Cleamentioning
confidence: 86%
See 3 more Smart Citations